2012
DOI: 10.4049/jimmunol.1102244
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biologic Characterization of Exosomes and Microvesicles as Facilitators of HIV-1 Infection in Macrophages

Abstract: Exosomes and microvesicles (MV) are cell membranous sacs originating from multivesicular bodies and plasma membranes that facilitate long-distance intercellular communications. Their functional biology, however, remains incompletely understood. Macrophage exosomes and MV isolated by immunoaffinity and sucrose cushion centrifugation were characterized by morphologic, biochemical, and molecular assays. Lipidomic, proteomic, and cell biologic approaches uncovered novel processes by which exosomes and MV facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
196
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(203 citation statements)
references
References 47 publications
3
196
2
2
Order By: Relevance
“…Several studies have reported that virus biogenesis and release converge with EV pathways, suggesting an evolutionary conserved system of virus-EV codependence (35)(36)(37)(38)(39). In fact, exosomes may be regarded as endogenous viruses as they have been shown to transfer various classes of nucleic acids (2)(3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that virus biogenesis and release converge with EV pathways, suggesting an evolutionary conserved system of virus-EV codependence (35)(36)(37)(38)(39). In fact, exosomes may be regarded as endogenous viruses as they have been shown to transfer various classes of nucleic acids (2)(3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this immune evasion strategy via secreted MPs has been previously described for other viruses. Microvesicles released from infected cells facilitate the spread of human immunodeficiency virus and herpes simplex virus to neighboring uninfected cells by transferring either viral constituents or the host's membrane proteins required for viral entry to other null cells, thereby increasing the number of susceptible cells (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, macrophages, which share the hematopoietic origin, func- tional phenotypes, and markers with microglia and are virtually undistinguishable from brain resident myeloid cells in the inflamed brain [24 -30], can be easily expanded in vitro and efficiently release MVs during pathological processes, such as viral infection [31] and cancer [32].…”
Section: Discussionmentioning
confidence: 99%